Reconstruction of the Negative Publication System for Land Registration to Achieve Legal Certainty and Legal Protection for Rights Holders - Anggiat Tobing; Megawati Barthos (Journal Customary Law, 2026)
The land registration publication system plays a crucial role in establishing legal certainty, rights protection, and the stability of land transactions. Indonesia implements a negative publication system with a positive tendency, in which land certificates are recognized as strong evidence but remain open to lawsuits. This situation creates a paradox between the need for legal certainty and the demands of substantive justice, as certificate holders who have legally obtained rights still have the potential to face disputes in court. This study aims to analyze the construction of the land registration publication system in Indonesia, identify problems that affect legal certainty and protection, and formulate a reconstruction model that is more responsive to developments in legal practice and the digitalization of land administration. The research method used is normative juridical with a statutory, conceptual, and comparative legal approach. The analysis is conducted on the national regulatory framework, land law doctrine, and judicial practice, which demonstrates differing interpretations of the evidentiary power of certificates. The results of the study indicate that the main weaknesses lie in the absence of strong state guarantees, regulatory fragmentation, and suboptimal protection for buyers in good faith. The reconstruction of the publication system is aimed at a hybrid model that strengthens positive elements without neglecting corrective mechanisms, the development of a compensation scheme based on state responsibility, and the harmonization of regulations that support the integration of digital land registry systems. A comparative approach to the Torrens system in Australia and continental European registration models provides lessons on the importance of rigorous initial verification, data transparency, and clear assurance mechanisms to increase public trust in the land registration system.